Sustainability Report, Good Corporate Governance Dan Kinerja Keuangan: Studi Kasus Perusahaan Pertambangan Di Indonesia - Febrina Zega; Murni Dahlena Nasution; Debbi Chyntia Ovami (Jurnal Riset Akuntansi dan Bisnis, 2023)
Sustainability Report and Good Corporate Governance are corporate governance that provide information regarding economic, environmental and social activities and status to stakeholders both within and outside the Company. This study aims to examine the effect of sustainability reports and good corporate governance on financial performance proxied by return on assets (ROA). The objects of this research are mining companies listed on the IDX which issue consecutive annual financial reports in 2020-2022. The research sampling technique used a purposive sampling method, namely the selection of samples based on criteria. The sample of this research is 15 companies so that it obtains 45 observations. Data analysis technique uses multiple linear regression method (multiple linear regression method). Data processing uses panel data regression with the help of eviews 10 software. The results of this study indicate that economic aspects, independent board of commissioners have a significant positive effect on financial performance while environmental aspects, social aspects, managerial ownership do not have a significant effect on financial performance. Based on the results of the simultaneous test (f test) shows that Economic Aspects, Environmental Aspects, Social Aspects, Independent Board of Commissioners and Managerial Ownership have an effect on Financial Performance